Barriers and enablers in nursing students` clinical placement in a rural area with an indigenous population, a short communication - Nina B. Cheetham; Bente Norbye (International Journal of Circumpolar Health)
This article explores the challenges and opportunities for nursing students during clinical placements in rural areas with Indigenous and minority populations, specifically focusing on the Sami and Kven communities in Northern Norway. It highlights the importance of cultural sensitivity and competence in nursing education, as emphasised by the National Framework for Nursing and Health Professional Education. The Arctic Samprax project, utilising an action research approach, aims to develop sustainable practice models that integrate cultural sensitivity into nursing students’ learning experiences. The study reveals that explicit supervision and reflective dialogue are crucial for students to understand and address cultural aspects in healthcare. Challenges such as staff shortages, inconsistent supervision, and lack of continuity hinder the learning process. The article emphasises the need for collaboration between educational institutions and rural practice sites to enhance students’ cultural competence. Recommendations include developing preparatory programs focusing on the learning outcomes relevant for rural practice placements, as well as increasing practice placements in Indigenous areas. The study underscores the responsibility of educational institutions in circumpolar regions to contribute to inclusive and equitable healthcare services for diverse populations. We suggest a greater focus on cultural humility in the curriculum to align with the ethical guidelines for nurses.